Masyarakat Madani Dan Pendidikan Islam (Mengkonstruksi Masyarakat Madani Melalui Pendidikan Islam) - Asrori, Mohammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Nowadays, talking about madani society in the modern era is a need that must be realized soon. Modern society who does not have religion will always be worried, fihtened, and confuse. Therefore, madani society is a peace solution in diversity. Thus, the main goal of education reformagenda is the establishment of madani society. In other word, upholding the values of the sublime social relationship, such as tolerance, and pluralism is a continuation of upholding the values of civilization. With the award, the willingness to look on the others, however the differences that exists without overbearing each other, opinions or views themselves. Keywords: Madani society, Islamic education.